Mobile cellular subscriptions and economic growth : empirical evidence from panel data - Narmatha, Kaneasan (2021)
The purpose of this study is to examine the correlation between the economic growth and the variables influencing the growth. This study employs a panel data from 12 countries. The objective of this paper is to investigate the relationship between mobile cellular subscriptions and economic growth and whether Covid-19 has an impact on the mobile cellular subscriptions. Furthermore, the study primarily focuses on the importance of technology advancement as it plays a major role in the economic growth. This study uses GDP per capita as the proxy for economic growth which is dependent variable and mobile cellular subscriptions (MCS), inflation (CPI), Foreign Direct Investment (FDI), trade openness (TO), fixed telephonesubscriptions (FTS) and Covid-19 (C19) as the explanatory variables. Panel Least Squares and GMM are applied to analyse the data collected to determine the significance of the independent variables with the dependent variable. From the results obtained in the first three models, the study infers that mobile cellular subscriptions has a positively significant influence on the economic growth regardless whether it is estimated alone or with other macroeconomic variables. In the fourth model, the study concludes that Covid-19 does have an impact on the mobile cellular subscriptions. Hence, the overall outcome will give an overview of the variables that the government should focus on to promote economic growth in Malaysia. In addition, policy makers should consider advancing more utilization cellular technology which subsequently increases the demand and usage of mobile phones with cellular subscriptions. In a nut shell, technological advancements in the country should be given more priority